Genome-Wide Analyses of Repeat-Induced Point Mutations in the Ascomycota - van Wyk, Stephanie; Wingfield, Brenda D.; De Vos, Lieschen; van der Merwe, Nicolaas A.; Steenkamp, Emma T. (Frontiers in Microbiology, 2021)
The Repeat-Induced Point (RIP) mutation pathway is a fungus-specific genome defence mechanism that mitigates the deleterious consequences of repeated genomic regions and transposable elements (TEs). RIP mutates targeted sequences by introducing cytosine to thymine transitions. We investigated the genome-wide occurrence and extent of RIP with a sliding window approach. Using genome-wide RIP data and two sets of control groups, the association between RIP, TEs, and GC content were contrasted in organisms capable and incapable of RIP. This study further set out to determine the extent and occurrence of RIP in 58 Ascomycota. The findings were summarized by placing each of the Ascomycota representatives in one of six categories based on the extent of genome-wide RIP. In silico RIP analyses, using a sliding-window approach with stringent RIP parameters, implemented simultaneously within the same genetic context, on high quality genome assemblies, yielded superior results in determining the genome-wide RIP amongst the Ascomycota. Most Ascomycota had RIP and was particularly widespread among classes of the Pezizomycotina, including the early diverging Orbiliomycetes and the Pezizomycetes. The most extreme cases of RIP were limited to representatives of the Dothideomycetes and Sordariomycetes. By contrast, the genomes of the Taphrinomycotina and Saccharomycotina contained no detectable evidence of RIP. Also, recent losses in RIP combined with controlled TE proliferation in the Pezizomycotina subphyla may promote substantial genome enlargement as well as the formation of sub-genomic compartments. These findings have broadened our understanding of the taxonomic range and extent of RIP in Ascomycota and how this pathway affects the genomes of fungi harbouring it.